Endowing Orthopedic Implants’ Antibacterial, Antioxidation, and Osteogenesis Properties Through a Composite Coating of Nano-Hydroxyapatite, Tannic Acid, and Lysozyme - Wang, Guofeng; Zhu, Yaxin; Zan, Xingjie; Li, Meng (Frontiers in Bioengineering and Biotechnology, 2021)
Abstract There is a substantial global market for orthopedic implants, but these implants still face the problem of a high failure rate in the short and long term after implantation due to the complex physiological conditions in the body. The use of multifunctional coatings on orthopedic implants has been proposed as an effective way to overcome a range of difficulties. Here, a multifunctional (TA@HA/Lys)n coating composed of tannic acid (TA), hydroxyapatite (HA), and lysozyme (Lys) was fabricated in a layer-by-layer manner, where TA deposited onto HA firmly stuck Lys and HA together. The deposition of TA onto HA, the growth of (TA@HA/Lys)n, and multiple related biofunctionalities were thoroughly investigated. Our data demonstrated that such a hybrid coating displayed antibacterial and antioxidant effects, and also facilitated rapid attachment of cells (both mouse embryo osteoblast precursor cells (MC3T3-E1) and dental pulp stem cells (DPSCs)) in the early stage and their proliferation over a long period. This accelerated osteogenesis in vitro and promoted bone formation in vivo. We believe that our findings and the strategy developed here could pave the way for multifunctional coatings not only on orthopedic implants, but also for additional applications in catalysts, sensors, and tissue engineering, among others.